Study of the chemical and bactericide interaction of zinc oxide nanoparticles against Staphylococcus aureus - Zegarra Pumacayo, Jorge Luis (2021)
The waters of rivers, seas and lagoons contaminated by various sources, whether of natural or anthropogenic origin, contain polluting substances, among them they present a high bacterial load, which does not allow human consumption because it causes damage to human health. Therefore, the research carried out presents the study of the photocatalytic effect of zinc oxide nanoparticles (ZnONPS) as its mechanism of biochemical interaction with the consequent formation of reactive oxygen substances (ROS) and thus propose the interpretation of its subsequent Bactericidal effect by generating cellular damage in Staphylococcus aureus bacteria. According to the results obtained in an experimental pilot work, the decrease in colony formation evaluated through the plate culture method was reported, and it was determined that the concentration of 10- 4 g of ZnONPs/ mL of ZnO nanoparticles (synthesized by the precipitation method) of size 29 nm against Staphylococcus aureus bacteria ATCC 25923 presented an amount less than 1 CFU / g at the end of the analysis.